Evidence for superior neurobiological and behavioral inhibitory control abilities in non‐offending as compared to offending pedophiles. Issue 2 (21st October 2016) - Kärgel, Christian; Massau, Claudia; Weiß, Simone; Walter, Martin; Borchardt, Viola; Krueger, Tillmann H.C.; Tenbergen, Gilian; Kneer, Jonas; Wittfoth, Matthias; Pohl, Alexander; Gerwinn, Hannah; Ponseti, Jorge; et al.
Abstract: Neurobehavioral models of pedophilia and child sexual offending suggest a pattern of temporal and in particular prefrontal disturbances leading to inappropriate behavioral control and subsequently an increased propensity to sexually offend against children. However, clear empirical evidence for such mechanisms is still missing. Using a go/nogo paradigm in combination with functional magnetic resonance imaging (fMRI) we compared behavioral performance and neural response patterns among three groups of men matched for age and IQ: pedophiles with ( N = 40) and without ( N = 37) a history of hands‐on sexual offences against children as well as healthy non‐offending controls (N = 40). As compared to offending pedophiles, non‐offending pedophiles exhibited superior inhibitory control as reflected by significantly lower rate of commission errors. Group‐by‐condition interaction analysis also revealed inhibition‐related activation in the left posterior cingulate and the left superior frontal cortex that distinguished between offending and non‐offending pedophiles, while no significant differences were found between pedophiles and healthy controls. Both areas showing distinct activation pattern among pedophiles play a critical role in linking neural networks that relate to effective cognitive functioning. Data therefore suggest that heightened inhibition‐related recruitment of these areas as well as decreased amount of commission errors is related to better inhibitory control in pedophiles who successfully avoid committing hands‐on sexual offences against children. Hum Brain Mapp 38:1092–1104, 2017 . ©2016 Wiley Periodicals, Inc.